Efficacy of single‐dose and double‐dose ivermectin early treatment in preventing progression to hospitalization in mild COVID‐19: A multi‐arm, parallel‐group randomized, double‐blind, placebo‐controlled trial - Mirahmadizadeh, Alireza; Semati, Ali; Heiran, Alireza; Ebrahimi, Mostafa; Hemmati, Abdolrasool; Karimi, Mohammadreza; Basir, Souzan; Zare, Marjan; Charlys da Costa, Antonio; Zeinali, Mohammad; Sargolzaee, Maryam; Eilami, Owrang (Respirology (Carlton, Vic.), 2022)
Background and objective Ivermectin is a known anti‐parasitic agent that has been investigated as an antiviral agent against coronavirus disease 2019 (COVID‐19). This study aimed to evaluate the efficacy of ivermectin in mild COVID‐19 patients. Methods In this multi‐arm randomized clinical trial conducted between 9 April 2021 and 20 May 2021, a total of 393 patients with reverse transcription‐PCR‐confirmed COVID‐19 infection and mild symptoms were enrolled. Subjects were randomized in a 1:1:1 ratio to receive single‐dose ivermectin (12 mg), double‐dose ivermectin (24 mg) or placebo. The primary outcome was need for hospitalization. Results There was no significant difference in the proportion of subjects who required hospitalization between the placebo and single‐dose ivermectin groups (absolute difference in the proportions: −2.3 [95% CI = −8.5, 4.1]) and between the placebo and double‐dose ivermectin groups (absolute difference in the proportions: −3.9 [95% CI = −9.8, 2.2]). The odds of differences in mean change in severity score between single‐dose ivermectin and placebo groups (ORdifference = 1.005 [95% CI: 0.972, 1.040]; p = 0.762) and double‐dose ivermectin and placebo groups (ORdifference = 1.010 [95% CI: 0.974, 1.046]; p = 0.598) were not statistically significant. None of the six adverse events (including mild dermatitis, tachycardia and hypertension) were serious and required extra action. Conclusion Single‐dose and double‐dose ivermectin early treatment were not superior to the placebo in preventing progression to hospitalization and improving clinical course in mild COVID‐19. We conducted a double‐blinded randomized placebo‐controlled trial including 393 patients with mild coronavirus disease 2019 (COVID‐19) and found that ivermectin, an anti‐parasitic medication with known antiviral properties, was non‐superior to the placebo. Neither a single nor a double dose was better in preventing progression to hospitalization and worsening of the clinical course of COVID‐19 infection.